Creativity teaching through e-book reading program among the children in Malaysia - Chew, F.P.; Eau, K.L (2016)
This study was carried out to identify the effectiveness of the literature lesson plans through E-picture book reading designed on the creativity elements; originality, elaboration and fluency. They were 42 children year 4-to-5-year old children from two private preschools in the district of Petaling Jaya, Selangor. This experimental research applied the Wallis Model of Creativity (1926) as the research framework and the Torrance Test of Creative Thinking (TTCT) as the instrument of study. Data was analyzed by using Statistical Package for the Social Science (SPSS). Findings indicated that there was significant difference between pre-test and post-test that carried out among the children in originality, elaboration and fluency elements of creativity with the total moderate effect size at .61. Chinese female children score higher than Malay male children in creativity. In other words, literature lesson plan through E-picture book reading is effective to inculcate the creativity among the children at the young age. Thus, the preschools and the educators should review their educational system to cultivate the creativity elements since creativity is an important criterion to produce dedicated leaders in the future.